2023
DOI: 10.3389/fimmu.2023.1282890
|View full text |Cite
|
Sign up to set email alerts
|

The dysregulation of immune cells induced by uric acid: mechanisms of inflammation associated with hyperuricemia and its complications

Delun Li,
Siyu Yuan,
Yiyao Deng
et al.

Abstract: Changes in lifestyle induce an increase in patients with hyperuricemia (HUA), leading to gout, gouty arthritis, renal damage, and cardiovascular injury. There is a strong inflammatory response in the process of HUA, while dysregulation of immune cells, including monocytes, macrophages, and T cells, plays a crucial role in the inflammatory response. Recent studies have indicated that urate has a direct impact on immune cell populations, changes in cytokine expression, modifications in chemotaxis and differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 125 publications
(186 reference statements)
0
4
0
Order By: Relevance
“…On the one hand, UA can induce cell damage through the activation of inflammatory responses and oxidative stress. On the other hand, UA can also affect the function of the immune system, including leukocyte migration and cytokine production (6). Therefore, UA may play a role in regulating the development of sepsis-induced inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, UA can induce cell damage through the activation of inflammatory responses and oxidative stress. On the other hand, UA can also affect the function of the immune system, including leukocyte migration and cytokine production (6). Therefore, UA may play a role in regulating the development of sepsis-induced inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicated that the initial serum UA levels during hospitalization should serve as a predictive indicator for the prognosis of sepsis in the pediatric intensive care unit (ICU) (5). Serum UA may play an important role in inflammatory responses, oxidative stress, and immune regulation (6). Inflammation caused an increase in the release of purines within cells, which in turn promoted the production and release of UA (7).…”
Section: Introductionmentioning
confidence: 99%
“…Dehydration and acidic urinary pH also favour the precipitation of urate, obstructing the collecting ducts and increasing intrarenal pressure, with a reduction in blood flow and renal glomerular filtration rate (GFR) [ 11 , 12 ]. Tissues damaged by crystals act as a lure for the initiation of the inflammatory response and, ultimately, cell death [ 13 , 14 , 15 ]. In addition to obstruction and oxidative stress, UA causes endothelial dysfunction due to a reduction in nitric oxide, renal vasoconstriction, loss of autoregulation, activation of angiotensin II, reduction in glomerular filtration, hypertension, renal ischaemia and activation of the immune system [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In immune cells, high uric acid is shown to promote ferroptosis of immune cells. Uric acid crystals can accumulate in target organs, leading to the development of systematic inflammation, activation of immune cells and induce oxidative stress ( 4 , 5 ). Burnier discussed in the current research topic the role of gout and hyperuricaemia and their epidemiological and genetic associations with CVDs.…”
mentioning
confidence: 99%